Optimizing Care and Outcomes for People with Type 2 Diabetes – Lessons from a Translational Research Program on Insulin Initiation in General Practice - Furler, John; Blackberry, Irene; Manski-Nankervis, Jo-Anne; O’Neal, David; Best, James; Young, Doris (Frontiers in Medicine, 2015)
Background Clinical inertia, failure to intensify treatment according to evidence-based guidelines, leads to prolonged, avoidable hyperglycaemia in people with type 2 diabetes (T2D). This is a challenge for General Practice (GP) and Primary Care, where most people with T2D receive most of their care. Sustained, integrated translational research programs are needed to embed effective treatments in routine practice, yet many challenges exist to developing such programs. Objectives To explore challenges and facilitators to implementing a translational research program focused on insulin initiation and titration among people with T2D in GP and to identify key factors important to support and sustain such translation research in primary care. Operationalising a program of translational work in primary care We describe a series of studies on insulin initiation and titration in GP including theory and qualitative work (Phase 1), a small feasibility and acceptability pilot (Phase 2), a large scale pilot (Phase 3), and a pragmatic cluster randomised trial currently under way (Phase 4). We used mixed methods to explore practice level implementation issues, and reflective investigator discussions to explore broader research program sustai